2021
DOI: 10.3390/biom11101419
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Insights into α-Synuclein Fibril Polymorphism

Abstract: Abnormal accumulation of aggregated α-synuclein (α-Syn) is seen in a variety of neurodegenerative diseases, including Parkinson’s disease (PD), multiple system atrophy (MSA), dementia with Lewy body (DLB), Parkinson’s disease dementia (PDD), and even subsets of Alzheimer’s disease (AD) showing Lewy-body-like pathology. These synucleinopathies exhibit differences in their clinical and pathological representations, reminiscent of prion disorders. Emerging evidence suggests that α-Syn self-assembles and polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 331 publications
(635 reference statements)
2
28
0
Order By: Relevance
“…It is a more reasonable assertion that, for a given amyloidogenic protein, a distribution of fibril morphologies characterizes the influence of lipids on fibril formation by that protein. Evidence to support this assertion arises from the observation that polymorphism of fibrils of α-Syn ( 113 , 115 , 116 ), hIAPP ( 117 ), Aβ seeded from AD brain amyloid ( 111 , 112 ) and obtained ex vivo ( 118 ), plus other proteins ( 118 , 119 ), is often found within material isolated from the same natural sample. In addition, the morphologies of Aβ filaments and aggregates are influenced by the presence of lipid membranes and their lipid composition ( 19 , 26 , 27 ).…”
Section: When and How Are Lipids Incorporated Into Fibrils?mentioning
confidence: 99%
“…It is a more reasonable assertion that, for a given amyloidogenic protein, a distribution of fibril morphologies characterizes the influence of lipids on fibril formation by that protein. Evidence to support this assertion arises from the observation that polymorphism of fibrils of α-Syn ( 113 , 115 , 116 ), hIAPP ( 117 ), Aβ seeded from AD brain amyloid ( 111 , 112 ) and obtained ex vivo ( 118 ), plus other proteins ( 118 , 119 ), is often found within material isolated from the same natural sample. In addition, the morphologies of Aβ filaments and aggregates are influenced by the presence of lipid membranes and their lipid composition ( 19 , 26 , 27 ).…”
Section: When and How Are Lipids Incorporated Into Fibrils?mentioning
confidence: 99%
“…Therefore, the anatomical origin of the spatial spread, its dynamics, and the affected brain regions have all attracted enormous interest to experimentally identify links between disease progression features and specific α-Syn fibril strains [15,[35][36][37][38][39][40]. For recent reviews see [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Various evidence has shown that the synuclein fibrils of synucleinopathies, which include MSA, Parkinson's disease, Parkinson's disease with dementia, and dementia with Lewy bodies (DLB) are distinct (Schweighauser et al, 2020). The diversity of fibril structure has also shown us that the polymorphism of fibrils can cause significant differences in biological activity and clinical pathology (Boyer et al, 2020;Healey et al, 2016;Shewmaker et al, 2011;Tycko, 2015) (Falcon et al, 2018;Mehra et al, 2021;Schweighauser et al, 2020). We hypothesize that the structural variation in fibril structures could lead to different disease pathologies, and thus plan to explore structures of mutant synuclein fibrils to elucidate the structure activity relationship of synuclein fibrils in toxicity and pathology.…”
Section: Discussionmentioning
confidence: 99%